2013
DOI: 10.1037/a0032869
|View full text |Cite
|
Sign up to set email alerts
|

Separation anxiety in families with emerging adults.

Abstract: In several developmental theories separation anxiety has been identified as an important feature of close interpersonal relationships. Most often, separation anxiety has been examined in the context of mother-child dyads in infancy. Increasingly, however, it is recognized that separation anxiety is also relevant in other relationships (e.g., the father-child relationship) and in later developmental periods (e.g., adolescence and emerging adulthood). The present study aimed to investigate separation anxiety at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 56 publications
2
32
1
Order By: Relevance
“…Findings of the review also underscored the specificity of separation anxiety as a typical feature of the mother–child dyad (Kins, Soenens, & Beyers, 2013). These results are in line with the literature (Arnett, 2015; McGoldrick, Heiman, & Carter, 1993; Scabini, 2000), which suggests that mothers play a core role in the parent–child relationship and tend to be more involved in their children's lives than fathers are.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 83%
“…Findings of the review also underscored the specificity of separation anxiety as a typical feature of the mother–child dyad (Kins, Soenens, & Beyers, 2013). These results are in line with the literature (Arnett, 2015; McGoldrick, Heiman, & Carter, 1993; Scabini, 2000), which suggests that mothers play a core role in the parent–child relationship and tend to be more involved in their children's lives than fathers are.…”
Section: Family Dynamics During Emerging Adulthood: What We Already Knowmentioning
confidence: 83%
“…In fact, studies in recent years have shown that parents support their "children" for too long (Seiffge-Krenke, 2006, 2009 and accompany their steps into adult life with anxious monitoring (Soenens & Vansteenkiste, 2010). According to the study by Kins, Soenens, and Beyers (2013), parental anxiety ("separation anxiety") has a significant negative effect on the identity development of adult children and also leads to high symptom severity of the "children." In sum, these unfavorable parental behaviors were linked to delays in identity development and compromise the mental health of the offspring (Klimstra & Denissen, 2017).…”
Section: Individual and Family Factors Influencing Identity Developmentmentioning
confidence: 99%
“…Hudson and Rapee (2005) noted that the family environment was latently influential during the development of some mental disorders, and other studies have identified that marriage conditions and family environment affect adolescents and emerging adults -particularly with regard to separation anxiety (Kins, Soenens, & Beyers, 2013). Family environment can also relate to anxiety disorder through cognitive mediation, a model that suggests perceived control is a mediator of the relationship between negative affect and family environment, and a controlling family environment arising from negative affect in turn affects anxiety (Chorpita, Brown, & Barlow, 1998).…”
mentioning
confidence: 99%